Let the first number be x.
The second number is 5 times less than x => x - 5
Therefore, we can write the statement as
![\begin{gathered} x*(x-5)=-4 \\ x^2-5x=-4 \\ \therefore \\ x^2-5x+4=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/o5u7oa7kjxm4rkmlhi7trmt40ve3pktu0a.png)
Solving the quadratic equation:
Let us replace -5x in the equation with -4x and -x to be able to factorize.
Hence,
![\begin{gathered} x^2-4x-x+4=0 \\ x(x-4)-1(x-4)=0 \\ (x-4)(x-1)=0 \\ \text{Therefore} \\ x-4=0\text{ } \\ or \\ x-1=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jsrg8342l6kk5c1z0rj6seoung9eqksmb4.png)
Hence,
![\begin{gathered} x=1 \\ or \\ x=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wta9r8zy1yyuojw7n8443zhri6eiuzulc7.png)
Therefore, the number can be 1 or 4.
The second number can be
![\begin{gathered} 1-5=-4 \\ or \\ 4-5=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/o6ays7scj19r59bk6029x23860s34lpujc.png)
Therefore, the pair of numbers can be
![(1,-4)\text{ or (4, -1)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/o5kqqenn716t9obeftnic4pdse120rut7w.png)